SARCASM HUMOR IN HABIB JA'FAR'S LOG-IN CONTENT ON DEDDY CORBUZIER'S YOUTUBE CHANNEL - Anjayuni, Efa; Malayati, Robi'ah Machtumah; Rahmah, Shofa Nadya (Universitas Islam Negeri Mataram, 2024)
Sarcasm in this study is represented through language signs in Habib Ja'far's da'wah on Log-In content on Deddy Corbuzier's YouTube account. This research uses an interpretive qualitative method through Ferdinand de Saussure's semiotics to analyze the signs and meaning of da'wah language. The results showed that Habib Ja'far's da'wah is propositional Sarcasm, Lexical Sarcasm, 'Like'-Prefixed Sarcasm, Illocutionary Sarcasm. Habib Ja'far's sarcastic humor aims to reduce tension and sensitivity to sensitive issues related to religion, social, and culture. Habib Ja'far's use of sarcastic humor serves to create a lighter and more open atmosphere without offending, aiming to reduce tension and sensitivity to sensitive issues related to religion, social, and culture.